2018
DOI: 10.4236/as.2018.99082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental and Microclimate Factors on the Coffee Beans Quality (C. canephora): Correlation between Chemical Analysis and Stable Free Radicals

Abstract: The present study reports a physicochemical comparison of shade-grown and sun-grown coffee beans, under unripe, rip and roasted-ripe conditions, using electrical conductivity measurements, electron paramagnetic resonance (EPR), infrared spectroscopy (FTIR), and high performance liquid chromatography (HPLC). Moreover, the assessed physicochemical parameters were compared with organoleptic evaluations based on the Coffee Quality Institute protocol. The values found for electrical conductivity, leached potassium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…green and (b) roasted. Assessed g-factors were in the range of 2.0043 -2.0045, with a peak-to-peak line width of about 0.65 mT; these parameters are characteristic of stable free radical species previously described in coffee beans [22,24].The quantitative assessment of stable free radicals was carried out by double integrating the EPR spectra (intensity) and the results are collected in Table 2. Relative values vary in the range of 0.032 -0.083 a.u.…”
Section: Stable Free Radicalsmentioning
confidence: 95%
See 4 more Smart Citations
“…green and (b) roasted. Assessed g-factors were in the range of 2.0043 -2.0045, with a peak-to-peak line width of about 0.65 mT; these parameters are characteristic of stable free radical species previously described in coffee beans [22,24].The quantitative assessment of stable free radicals was carried out by double integrating the EPR spectra (intensity) and the results are collected in Table 2. Relative values vary in the range of 0.032 -0.083 a.u.…”
Section: Stable Free Radicalsmentioning
confidence: 95%
“…Taking this into account, the measured contents of 5-CQA (Table 1),for the studied genotypes, are in the range of47.2 -56.9 mg/g. BICHO et al [24,39] found values of 44.3 mg/g and 47.0 mg/g, respectively for the species Arabica (Brazil) and Robusta (India), where as ALVES et al [39] obtained values in the range of 44.8 -49.3 mg/g for Brazilian Robusta beans. From the results herein obtained, the genotypes Bamburral and Coringa present lower contents of this compound, whereas the others genotypes, with higher fractions, did not present statistical differences (p ≤ 0.05).…”
Section: Chemical Characterizationmentioning
confidence: 95%
See 3 more Smart Citations